A comparative analysis of crop water footprint, practices, and economic water productivity (EWP) in Punjab, Pakistan and Western Australia, Australia - Zohreh Rajabi; Stephen Gray; Shakeel Hayat; Muhammad Atiq Ur Rehman Tariq (Irrigation Science, 2026)
A comprehensive analysis of crop water footprint (WFP), water use efficiency (WUE) and economic water productivity (EWP) between 2010 and 2020 in two climatically and economically diverse agricultural regions: Punjab, Pakistan and Western Australia, Australia was undertaken. Using the Water Footprint Network method and climate, soil and agricultural production data, the study quantified green, blue and grey water footprints for five staple crops in each region. Normalization by local water scarcity and irrigation share was used to compare between the two regions with different water stress levels and irrigation dependence. Results showed that the total crop water requirements in Punjab increased by 12% during the study period due to changing climatic conditions. Cotton and rice had the highest WFP and dependence on irrigation, however generated relatively low economic returns per unit of water, showcasing inefficiency in the current agricultural system. In contrast, rain-fed crops in WA showed lower absolute crop water requirements and lower increases in normalized WFP, with stable WUE and EWP with cereals, showcasing efficient water use under climate-driven limitations. Normalization highlighted the difference in water stress, identifying that Punjab’s irrigation-intensive crops put much greater stress on local water resources than WA crops. Integration of biophysical and economic indicators, when normalizing for water scarcity, provides a strong basis to assess water practice of various agricultural systems. The results indicate the necessity for location-specific approaches: increased irrigation efficiency and suitable crop selection in Punjab; and climate-resilient cropping to maximize water use productivity and economic return in WA.

Temperature-responsive regulation of combined drip and micro-sprinkler systems in greenhouses: an EWM-TOPSIS approach for enhancing tomato heat resilience and irrigation efficiency - Chuan Zhang; Run Xue; Haofang Yan; Imran Ali Lakhiar; Jiangtao Ren; Kinde Negessa Disasa; Muhammad Akhlaq; Shuaishuai Deng (Irrigation Science, 2026)

Water footprint assessment under deficit irrigation: a comparative analysis of field data and CROPWAT model agreement in semi-arid regions - Hasan Er; Halit Tutar; Ilker Angin; Abdullah Muratoglu; Mehdi Rahimi; Muhammad Farooq (Irrigation Science, 2026)

Response of tomato growth and transpiration under adequate elevated CO2 concentrations coupled with irrigation regimes - Muhammad Akhlaq; Henglu Miao; Chuan Zhang; Run Xue; Haofang Yan; Muhammad Usman Hameed; Jun Li; Jiangtao Ren; Junaid Nawaz Chauhdary; Muhammad Mahmood Ur Rehman (Irrigation Science, 2025)

Identifying the optimum irrigation strategies to maximize canola yield and profitability under climate change in Guanzhong Plain, China - Qaisar Saddique; De Li Liu; Ali Ajaz; Bin Wang; Xiaobo Gu; Muhammad Adnan; Puyu Feng; Yunfei Wang; Yufeng Zou; Huanjie Cai (Irrigation Science, 2025)
Climate change has a substantial impact on Chinese canola production, introducing a high level of uncertainty regarding future climatic conditions and their potential impact on canola production and gross margins. This study focused on identifying the optimal irrigation strategy to enhance the profitability of canola production in the Guanzhong Plain under future climate change conditions. In this study, we used the calibrated Agricultural Production Systems sIMulator (APSIM)-Canola model with the downscaled daily climate projections from 27 general circulation models (GCMs). These simulations were conducted under two Shared Socio-economic Pathways scenarios (SSP245 and SSP585) to assess the impact of climate change on canola phenology, rainfed and irrigated crop yield. We also conducted a gross margin analysis to assess the profitability dynamics of supplying irrigation to rainfed canola crop. An increase in rainfed canola yield was observed for all simulation periods, with an average increase of 11%, 15%, and 17% for the 2030s, 2060s, and 2090s, respectively. Supplementary irrigation using a threshold of 10–60% of plant available water capacity (PAWC) was found to be effective. Overall, it led to a 28% increase in yield for rainfed and an 85% improvement in gross margin. Beyond the threshold of 60% PAWC, additional irrigation did not result in statistically significant increases in yield and gross margin. We identified the optimal amount of irrigation for achieving maximum water productivity (WP) ranges from 85 to 150 millimeters. By avoiding irrigation when the soil’s plant available water capacity (PAWC) is over 60%, up to 44% of water can be saved. These findings could be useful for policymakers and farmers in planning for sustainable and enhanced canola production in the region.

Modelling crop water demand under climate change: the case of Sardinia region - Muhammad Faizan Aslam; Sara Masia; Donatella Spano; Valentina Mereu; Marta Debolini; Richard L. Snyder; Andrea Borgo; Antonio Trabucco (Irrigation Science, 2025)

Modelling the long-term potential effects of modern irrigation systems on soil–water and salt balances, and crop-water productivity in semi-arid regions - Muhammad Hamed Khan; Ranvir Singh; Brent Clothier; Tonny Tessa de Vries (Irrigation Science, 2025)
Modernization of irrigation systems is considered to improve irrigation efficiency, save water, and increase crop yields in water-scare semi-arid regions. This study conducted a long-term (10-years) simulations evaluating the potential effects of three different irrigation scenarios on soil water and salt balances, and crop water productivity of cotton-wheat cultivation in the Hakra Branch Canal command of Punjab, Pakistan. The physically based agro-hydrological model, Soil–Water-Atmosphere-Plant (SWAP) was applied to simulate the long-term (2007–2017) effects of three irrigation scenarios; (1) current surface irrigation ( baseline reference ) based on local farmers observations, (2) improved precision surface irrigation system ( PSIS ), and (3) a high-efficiency irrigation system ( HEIS ). The HEIS scenario without a leaching fraction (noted as HEIS_noLF ), defined as using sprinkler irrigation to bring the soil back to the field capacity, resulted in about 48% less long-term average irrigation needs (830 mm yr −1 ) as compared to the baseline scenario (1590 mm yr −1 ). This reduction in irrigation, however, resulted into a relatively higher average soil salt build-up (as 35 mg cm −2 ) causing a reduction of 18%—30% in the wheat crop yields. The HEIS scenario with a leaching fraction (noted as HEIS_LF ), with an additional irrigation of 60 mm at the start of crop season followed by an additional 10 mm with each irrigation interval, reduced the average salt build up (as 13 mg cm −2 ) and its adverse effects of the crop yields. However, HEIS_LF scenario resulted in the similar average irrigation amounts (955 mm yr −1 ), soil water and salt balances, crop yields and water productivity values as achieved by the PSIS scenario, defined as a fixed depth of 80 mm surface irrigation at each flexible irrigation intervals. This suggests limited scope for irrigation savings by adopting high-efficiency irrigation systems, such as sprinkler, with marginal quality (> 0.9 dS m −1 ) irrigation waters in semi-arid regions of Pakistan. Application of an appropriate leaching fraction is essential for controlling soil salinity build-up from irrigations marginal and saline groundwater in the study area. This reduces any gain to be made by high-efficiency (such as sprinkler) irrigation systems to save irrigation waters. However, there appears scope of improving surface irrigation (e.g. PSIS ) by reducing irrigation depths (through field levelling) and introducing flexible irrigation scheduling, as compared to the current (baseline) irrigation practices.

Impact of irrigation schedule and integrated nutrient management on wheat yield and nutrients uptake under semi-arid regions - Murad Ali; Abdul Bari; Muhammad Ibrahim; Iftikhar Ahmed; Uzair Ahmed; Rabia Zafar; Waqas Ahmad; Muhammad Saeed; Muhammad Khalid (Irrigation Science, 2025)

Aerated drip irrigation improves watermelon yield, quality, water and fertilizer use efficiency by changing plant biomass and nutrient partitioning - Yunpeng Zhou; Jing He; Yanzheng Liu; Haisheng Liu; Tianze Wang; Yaxin Liu; Weijie Chen; Tahir Muhammad; Yunkai Li (Irrigation Science, 2023)

Formation mechanism for emitter composite-clogging in drip irrigation system - Yunkai Li; Ji Feng; Song Xue; Tahir Muhammad; Xiuzhi Chen; Naiyang Wu; Weishan Li; Bo Zhou (Irrigation Science, 2019)

Composite clogging characteristics of emitters in drip irrigation systems - Ji Feng; Yunkai Li; Zeyuan Liu; Tahir Muhammad; Ruonan Wu (Irrigation Science, 2019)

Impact of hydrodynamics on clay particle deposition and biofilm development in a labyrinth-channel dripper - Nassim Ait-Mouheb; Juliette Schillings; Jafar Al-Muhammad; Ryad Bendoula; Séverine Tomas; Muriel Amielh; Fabien Anselmet (Irrigation Science, 2019)

The potential of precision surface irrigation in the Indus Basin Irrigation System - Arif A. Anwar; Waqas Ahmad; Muhammad Tousif Bhatti; Zia Ul Haq (Irrigation Science, 2016)

Modeling a weak turbulent flow in a narrow and wavy channel: case of micro-irrigation - Jafar Al-Muhammad; Séverine Tomas; Fabien Anselmet (Irrigation Science, 2016)

Application of the CSM-CERES-Rice model for evaluation of plant density and irrigation management of transplanted rice for an irrigated semiarid environment - Shakeel Ahmad; Ashfaq Ahmad; Hakoomat Ali; Abid Hussain; Axel Garcia y Garcia; Muhammad Azam Khan; Muhammad Zia-Ul-Haq; Mirza Hasanuzzaman; Gerrit Hoogenboom (Irrigation Science, 2013)

Flexibility analysis of irrigation outlet structures using simulation of irrigation canal hydrodynamic model - Javaid A. Tariq; Muhammad Latif (Irrigation Science, 2011)

Factors affecting success and failure of trickle irrigation systems in Balochistan, Pakistan - Muhammad Akram Kahlown; William Doral Kemper (Irrigation Science, 2007)